Automated traffic light and speeding violation apprehension system - Alarcon, Francis Noel I. (Animo Repository, 2017)
Travelling from one area to another is an essential part of everyday living and affects every person in a geographic area. Hindrances such as accidents and neglect of rules and regulations have generated a huge impact not only financially but also the physical, psychological, social and the well-being of a person. The use of technology can help drastically improve the transport engineering and management in a country. The Philippines has been experiencing an increase of violations for the past years and solutions that have been proposed have minimized the problem but have not fully solved them. With the target of congestion-free by 2030 getting closer, implementations for intelligent transport system has become relevant in the recent years. The study in automated apprehension system can help in developing transport systems that can improve the traffic condition in the country. The objective of the study is to design and develop an Automated Traffic Light and Speeding Violation Apprehension System. This system will be used to detect and record violations of over speeding and traffic light violation, specifically beating the red light, committed by vehicles. The system is developed using the LabVIEW platform.